Influence of temperature and wavelength on optical behavior of copper alloys - Mann, Vincent; Hugger, Florian; Roth, Stephan; Schmidt, Michael (Applied Mechanics and Materials, 2014)
Quantitative measured values for absorption of copper and its alloys are jet unknown in the temperature range between 30 °C and 500 °C which has to be passed before material melts in the initial phase of laser beam welding. Thus this paper investigates temperature and wavelength dependent absorption for VIS and IR wavelengths. For this purpose specimens of copper and copper alloys are heated up and reflected laser light from the surface is measured by using an Ulbricht sphere in combination with a photodiode. During welding processes inert gases are in use to reduce oxidation. Hence the influence of shielding gases on the absorption will also be taken into account during the heating process of the specimens. Consequently this paper provides results for the temperature dependent absorption of copper and copper alloys for different wavelengths at atmospheric conditions and argon shielding.
Created from Fastlane, Scopus look-up
Keywords: Absorptivity; Continuous wave; Copper; Frequency-doubled; Inert gas; Infrared; Laser beam welding; Reflection; Ulbricht-sphere